Nurturing Conservation - Minded Behavior of Students of Agricultural Mechanization Program, Vocational School using Contextual Learning Strategy - ., Sudarman; ., Djuniadi; Sutopo , Yeri (KnE Social Sciences, 2019)
This study aims to ﬁgure out: (1) the implementation of contextual learning strategy in environmental education course; (2) the learning outcomes of the environmental education using contextual learning strategy during the debrieﬁng of the internship program; (3) conservation-minded behavior of the internship program participants; (4) the contribution of the environmental education learning outcomes using the contextual strategy in the internship program brieﬁng on the conservation – minded behavior. The study was conducted at SMK N 1 Bawen and industry in Semarang and its surrounding districts in 2018. The data on the implementation of contextual strategy during the internship program debrieﬁng were gathered using an observation sheet. The learning outcomes of the implementation of the contextual strategy in environmental education course during the debrieﬁng of the internship program were gathered using a test sheet and the data on the conservation-minded behavior of the internship program participants were gathered using an observation sheet. Data analysis was conducted using the descriptive analysis and simple regression. This results of the study showed that; (1) the contextual strategy was implemented by providing additional materials during the environmental education course; (2) the students’ learning outcomes of environmental education using the contextual strategy were mostly high; (3) the score of the conservation-minded behavior as the internship participants were high; (4) the contribution to the results of the contextual strategy implementation on the conservation education learning process was 86.8 percent to the conservation – minded behavior of the internship participants. Keywords: the contextual strategy, conservation-minded behavior